Upk3b is dispensable for development and integrity of urothelium and mesothelium. - Carsten Rudat; Thomas Grieskamp; Christian Röhr; Rannar Airik; Christoph Wrede; Jan Hegermann; Bernhard G Herrmann; Karin Schuster-Gossler; Andreas Kispert (PLoS ONE, 2014)
The mesothelium, the lining of the coelomic cavities, and the urothelium, the inner lining of the urinary drainage system, are highly specialized epithelia that protect the underlying tissues from mechanical stress and seal them from the overlying fluid space. The development of these epithelia from simple precursors and the molecular characteristics of the mature tissues are poorly analyzed. Here, we show that uroplakin 3B (Upk3b), which encodes an integral membrane protein of the tetraspanin superfamily, is specifically expressed both in development as well as under homeostatic conditions in adult mice in the mesothelia of the body cavities, i.e., the epicardium and pericardium, the pleura and the peritoneum, and in the urothelium of the urinary tract. To analyze Upk3b function, we generated a creERT2 knock-in allele by homologous recombination in embryonic stem cells. We show that Upk3bcreERT2 represents a null allele despite the lack of creERT2 expression from the mutated locus. Morphological, histological and molecular analyses of Upk3b-deficient mice did not detect changes in differentiation or integrity of the urothelium and the mesothelia that cover internal organs. Upk3b is coexpressed with the closely related Upk3a gene in the urothelium but not in the mesothelium, leaving the possibility of a functional redundancy between the two genes in the urothelium only.